Tuberculosis in the Tintswalo district of the Northern Province - Edginton, Mary E. (My University, 2014)
This study is divided into two phases, an historical record review and an intervention study.In the period 1992 to mid-1994, tuberculosis management and treatment outcomes were reviewed in the Tintswalo district of the Northern province, South Africa. Bacteriological coverage, diagnostic criteria and treatment outcomes for the 514 patients in this period were less than the internationally recommended goals, a record review giving a best estimate of treatment completion of 67% for new smear positive patients. An intervention study was set up from mid 1994 until January 1996. Twelve district clinics were randomised to either "treatment" or "control", depending on whether tuberculosis followup was at the hospital or clinics. Treatment clinic staff were trained, treatment supporters were organised, and the logistic needs of a good tuberculosis control programme (transport to the laboratory and drags supplies) were provided by the researchers, who collected data on patients, disease management and outcomes. A higher proportion of patients were diagnosed bacteriologically, the majority had supporters, and treatment outcomes for all new smear positive patients who lived in the district improved significantly to 81%. There was no change in outcomes for those living outside the boundaries of the study district. Successful treatment outcomes were more likely in supported patients, in new, as opposed to re-treatment patients,and in those with at least a minimum level of formal education. Patients were interviewed at different stages of their treatment. The results, together with those of focus group interviews on patients and other community members, provided insights into the problems experienced by patients, and their preferences, and into local beliefs and attitudes about this disease. It was concluded that good tuberculosis management in this rural district was possible, despite a number of constraints. It required commitment, staff training and support, management supervision, and organisation of a laboratory network and drug supplies.